Ectoparasite Infestation in Stray Cats at IPB Taman Kencana - Tetty Barunawati Siagian; Henny Endah Anggraeni; Dwi Budiono (Jurnal Pendidikan Indonesia, 2025)
IPB Taman Kencana Campus is one of IPB's campuses in the center of Bogor City. Its location in a public space and park area has led to an increase in the population of stray cats around this area. One problem found in stray cats on this campus is ectoparasite infestation. This study aims to investigate the presence of ectoparasite infestation in stray cats in the IPB Taman Kencana environment, Bogor. The study used 20 stray cats, consisting of 12 males and 8 females. The stray cats underwent physical examinations and ectoparasite identification. The results of the physical examinations showed that 100% of the stray cats were infested with ectoparasites, with more than one infestation or multiple infestations. The percentage of ectoparasite infestation in stray cats in the IPB Taman Kencana environment is 100% consisting of 90% infested with Ctenocephalides felis fleas, 55% infested with Otodectes cynotis mites, and 10% infested with Sarcoptes scabiei mites. Flea infestation is higher than mites, this is caused by direct contact between infected cats. High flea infestation in stray cats causes anemia, low BCS, thinness, stress, itching, dull hair, and baldness. Based on the results of the study, it was concluded that there was an ectoparasite infestation in stray cats in the IPB Taman Kencana environment with a high degree of infestation.